Association between a usual source of care and influenza vaccination rates among pregnant women. Issue 3 (21st December 2021) - Toth, Jennifer M.; Nsiah, Irene; Nair, Sonam; Ramachandran, Sujith
Abstract: Purpose: Pregnant women and infants less than 6 months of age have a higher risk of complications from influenza. Vaccination is recommended for pregnant women to decrease risk of infection and hospitalizations between both the women themselves and infants. However, vaccination rates remain low in pregnant women. The objective of this study was to determine the association between having a usual source of care and seasonal influenza vaccination rates among women who were pregnant between 2012 and 2016. Methods: A retrospective study was conducted using pooled data from the 2012–2016 Medical Expenditure Panel Survey. Frequencies of seasonal influenza vaccinations and other sociodemographic factors were estimated. A multivariable log‐binomial regression model was used to examine the association between having a usual source of care and seasonal influenza vaccination rates. Results: The weighted influenza vaccination rate among pregnant women was 54.5%. About one third did not have a usual source of care. The adjusted prevalence ratio of receiving an influenza vaccine for pregnant women without a usual source of care was 0.76 (95% confidence interval = 0.60–0.98). The top three main reasons for not having a usual source of care were being seldom or never sick (55.7%), not having health insurance (10.6%), and having recently moved to an area (9.9%). Conclusions: Pregnant women without a usual source of care had significantly lower probability of being vaccinated against seasonal influenza. Improving access to care through greater insurance coverage, addressing cost barriers, and providing patient education may help improve vaccination rates in this population.